Patient satisfaction with a clinically integrated sleep apnea care model vs. the current sleep care paradigm - Salinas, Gregory D.; Cerenzia, Wendy; Coleman, Brandon; Thorndike, Frances; Edington, Samantha; Riney, Heidi (Frontiers in Sleep, 2025)
IntroductionSleep apnea can have severe negative health effects, including cardiovascular diseases, metabolic disorders, and decreased quality of life. Continuous positive airway pressure (CPAP) therapy is highly effective and the gold standard treatment for sleep apnea; however, traditionally fragmented sleep healthcare has resulted in low levels of treatment adoption and adherence. A recent white paper analysis of traditional health plan claims found that a comprehensive model significantly outperformed traditional health plans with higher rates of adoption (80 vs. 49%), adherence (62 vs. 25%), and persistence (53 vs. 11%) to CPAP therapy, which resulted in lower total healthcare costs. To understand the patient experience in these models of care, this study compared patient satisfaction between the traditional sleep care approach and a clinically integrated, comprehensive sleep care program.MethodsA survey was developed to understand differences in the patient experience with the two different care models with respect to: access to sleep care, including time from initial appointment to seeing a sleep specialist, referral and insurance process; ease of sleep testing process and receiving a diagnosis; adoption, quality of education, and training with CPAP; ongoing adherence support with CPAP, and quality of life. Data were compared using descriptive statistics and Chi-square analyses.ResultsA significantly higher proportion of patients in the comprehensive model were satisfied with all measured points in the patient's journey. Notably, twice as many patients in the comprehensive model were very satisfied with: ease of navigating the testing process, time between diagnosis and CPAP adoption, insurance navigation for CPAP approval, and availability and level of ongoing CPAP support. Comprehensive care patients experienced fewer work disruptions due to sleep apnea: only 7% missed work in the past 3 months, compared to 58% in the traditional model.DiscussionOverall, the study highlights the benefits of a comprehensive care model in improving patient satisfaction with their sleep apnea journey and overall quality of life for individuals with sleep apnea. Pairing this positive patient experience data with prior data from the same treatment model shows that removing obstacles within a patient's journey positively impacts satisfaction while simultaneously improving adherence rates and reducing total healthcare costs.